Meralgia paresthetica after "all-in-one" appendectomy - Andrew M. Ng; Frankie B. Fike; Steven J. Schneider; Andrew R. Hong; Stephen E. Dolgin (Elsevier, 2015)
Minimally invasive approaches have become standard for pediatric appendectomy. The laparoscopic assisted single port approach, also known as the "all-in-one" appendectomy, has gained recent popularity [1]. We describe a child who suffered meralgia paresthetica (a neuropathy in the distribution of the lateral femoral cutaneous nerve) after a laparoscopic assisted single port appendectomy, perhaps secondary to mobilization of the cecum.